The Spot Market Matters : Evidence on Implicit Contracts from Britain - Paul J. Devereux; Robert A. Hart (Institute for the Study of Labor (IZA), 2005)
Based on the methodology of Beaudry and DiNardo (1991), this paper investigates the relative importance of the spot market and implicit contracts in the determination of British real wages. Empirical work is carried out separately for males and females with individuallevel data taken from the New Earnings Survey Panel for the years 1976 to 2001. In contrast to previous studies that used North American data, the spot market is found to be more important than implicit contracts in determining real wages. Indeed, there is very little support for implicit contracts in these data. Further evidence is provided through the analysis of individual wage sequences. These suggest that the downwardly rigid wage sequences implied by implicit contracts with costless worker mobility are not prevalent in Britain.
Keywords: E32; E24; J31; 330; spot market wages; implicit contracts; unemployment; wage sequences; Reallohn; Lohnbildung; Implizite Kontrakte; Arbeitslosigkeit; Schätzung; Grossbritannien